Is there a role for traditional and complementary medicines in managing chronic fatigue? a systematic review of randomized controlled trials - Li, Yuxiao; Yang, Jingya; Chau, Chi Ian; Shi, Junnan; Chen, Xianwen; Hu, Hao; Ung, Carolina Oi Lam (Frontiers in Pharmacology, 2023)
Introduction: Chronic fatigue syndrome (CFS) is an increasingly common condition that is challenging to treat due to unclear etiology and a lack of consensus on clinical diagnosis and treatment guidance. Many affected people resorted to using traditional and complementary medicines (T&CMs). However, the evidence for T&CMs for CFS has been inconclusive and continues to evolve. The study aims to identify, summarize and assess the most recent evidence on the efficacy and safety of T&CMs for CFS. Methods: Randomized controlled trials (RCTs) investigating T&CMs for CFS published in English of Chinese between 1 January 2013 and 31 December 2022 were searched from 7 databases. RCTs comparing T&CMs with no treatment, placebo, or pharmacological medicine were included, irrespective of language or blinding. The Consolidated Standards of Reporting Trials Statement extensions for Chinese herbal medicine Formulas (CONSORT-CHM) and the Cochrane Collaboration’s Risk of Bias tool were used to evaluate the quality and risk of bias of included studies. Results: A total of 62 RCTs investigating 43 types of T&CMs and involving 5,231 participants with CFS were included in this review. The primary outcome measures mainly included the scoring of fatigue symptoms using the validated tool Fatigue Scale-14 (FS-14) or the TCM syndrome score. The main interventions showing overall efficacy were Chaihu Guizhi Decoction and Buzhong Yiqi combined with Xiao Chaihu Decoction, and 148 ingredients were identified, including Astragali Radix, Glycyrrhizae Radix et Rhizoma, Atractylodis Macrocephalae Rhizoma, and Bupleuri Radix. The most significant effect was the improvement of fatigue, followed by TCM-diagnosed symptoms and other psychological conditions. No serious adverse effect had been reported. However, the quality of the RCTs included RCTs were found to be suboptimal, and the risk of bias remained uncertain. Conclusions: Some evidence from RCTs supported the efficacy and safety of T&CM in CFS. However, given the methodological and quality heterogenicity of the included studies, the recommendations of T&CMs in treating CFS remain inconclusive. To develop better quality evidence about T&CMs for CFS, future studies should employ more objective diagnosis standards and outcome measurements, larger sample size, and better bias control, and ensure the compliance with the corresponding reporting guidelines.